A method for strengthening a middle trough of an iron-based microalloy

CN122648932APending Publication Date: 2026-08-28ZHANGJIAKOU FUAN IND & TRADE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610810040.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-05
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

一是普通堆焊,如手工电弧焊,存在焊道结合强度低、易开裂、耐磨性能差的问题,使用寿命通常仅为3-6个月

Benefits of technology

1.结构创新:本发明采用莫比乌斯拓扑连续扭曲的焊道结构,可有效分散应力,消除传统焊道的应力集中点;同时,拓扑结构形成仿生螺旋流道,可减少煤岩粘附,降低粘附磨损。经测试,煤岩粘附率较传统网格焊道降低60%以上。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of surface strengthening of mining coal machine equipment parts, in particular to a kind of iron-based microalloy middle trough strengthening method, comprising: the pretreatment of middle trough matrix;Iron-based microalloy composite powder is prepared;Using Mobius topological scanning path and three-spot laser cladding process, bionic topological cladding layer is formed on the surface of matrix;Cladding layer is subjected to three-spot high-energy beam remelting treatment;Laser quenching is carried out on the non-cladding area of the bank, and gradient hardness layer is formed;Finally, post-processing is carried out.The beneficial effect is: the present application realizes the uniform dispersion of stress, the significant reduction of coal rock adhesion and the densification of cladding layer organization by the synergistic innovation of "structure-material-technology", the combination strength is high, the wear resistance, corrosion resistance is excellent, solve the problem of stress concentration, low bonding strength, high cost and short service life in the prior art, the service life is 3-4 times higher than traditional surfacing, suitable for the strengthening and remanufacturing of middle trough of coal mine scraper conveyor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of surface strengthening technology for components of mining coal mining equipment, specifically a method for strengthening iron-based microalloyed central grooves, and more particularly a method for strengthening the surface of central groove sides and chain tracks by combining Möbius topology, iron-based microalloyed materials, three-spot laser cladding, high-energy beam remelting, and laser quenching. Background Technology

[0002] The central trough is a core load-bearing component of the scraper conveyor in a fully mechanized coal mining face. Its sides and chain track directly experience friction, impact, and corrosion from the coal, rock, and scraper chain, resulting in an extremely harsh service environment. Currently, the industry primarily uses a single process to strengthen the central trough, which has the following technical shortcomings: Firstly, ordinary surfacing welding, such as manual arc welding, has problems such as low weld bond strength, easy cracking, and poor wear resistance, and its service life is usually only 3-6 months.

[0003] Secondly, conventional laser cladding often uses parallel or grid-like weld beads, which easily leads to stress concentration and rapid local wear; moreover, it often uses expensive nickel-based powder, making it uneconomical.

[0004] Third, single laser quenching can only improve the surface hardness of the substrate, and cannot take into account both wear resistance and corrosion resistance. In addition, it does not solve the problem of uneven stress distribution caused by unreasonable structural design.

[0005] Current technologies fail to integrate Möbius topology design with iron-based microalloy modification, three-spot gradient heat input processes, high-energy beam remelting, and laser quenching. This prevents the active regulation of stress distribution and coal-rock adhesion through topological structure, resulting in limited strengthening effects and high costs for the central trench, making it difficult to meet the long service life requirements of high-yield, high-efficiency mines. Therefore, developing a composite strengthening method for the central trench that combines high wear resistance, high corrosion resistance, high bonding strength, long service life, and low cost has become a pressing technical challenge in this field. Summary of the Invention

[0006] To overcome the technical deficiencies in the prior art and effectively solve the technical problems in the background art, the present invention provides the following technical solution: A method for strengthening the central groove of an iron-based microalloy includes the following steps: Step 1: Machin the sides of the middle channel and the surface of the chain track to remove oxide scale, oil stains, cracks and burrs. The surface roughness Ra is ≤ 3.2 μm. Then, ultrasonically clean with acetone for 10-15 min and dry for later use.

[0007] Step 2: Using iron-based alloy powder as the matrix, add microalloying elements to prepare iron-based microalloyed composite powder.

[0008] Step 3: Using a three-spot laser cladding process with a Möbius topology scanning path, the iron-based microalloy composite powder is clad onto the surface of the central tank substrate to form a Möbius topology cladding layer.

[0009] Step 4: Using a three-spot high-energy beam remelting process, the Möbius topology cladding layer is remelted in reverse along the Möbius topology scanning path.

[0010] Step 5: Laser harden the non-cladding area and the edge of the cladding layer in the middle groove sidewall to form a gradient hardness layer.

[0011] Step 6: Perform post-processing on the reinforced central groove, including mechanical polishing and inspection.

[0012] As a preferred embodiment of the present invention, the iron-based microalloy composite powder in step 2 comprises the following components by mass percentage: 12%-18% chromium, 3%-6% nickel, 2%-5% molybdenum, 1.5%-3.0% niobium, 0.5%-1.0% rare earth elements, with the balance being iron.

[0013] As a preferred embodiment of the present invention, the rare earth element is a lanthanum-cerium mixed rare earth element.

[0014] As a preferred technical solution of the present invention, the process parameters of the three-spot laser cladding in step 3 are as follows: total laser power 1800-2200W, of which the preheating spot accounts for 20%, the main cladding spot accounts for 60%, and the post-slow cooling spot accounts for 20%; scanning speed 15-25m / min; main spot diameter 3-5mm, preheating / slow cooling spot diameter 4-6mm, spot spacing 2-3mm; overlap rate 40%-55%; and the twist angle of the Möbius topology scanning path is 15°-30°.

[0015] As a preferred technical solution of the present invention, the process parameters of the three-spot high-energy beam remelting in step 4 are as follows: total power 900-1300W, of which the preheating spot accounts for 25%, the main remelting spot accounts for 50%, and the densification slow cooling spot accounts for 25%; scanning speed 10-20m / min; working pressure 50-100Pa; protective gas is argon with a flow rate of 20-30L / min; remelting depth 0.3-0.5mm.

[0016] As a preferred technical solution of the present invention, the laser quenching in step 5 has the following process parameters: laser power 800-1500W, scanning speed 5-10m / min, spot diameter 6-8mm, and quenching depth 0.8-1.2mm.

[0017] As a preferred technical solution of the present invention, in step 3, the three-spot laser cladding adopts a fiber laser and a three-spot shaping module, the preheating spot is triggered 1-2ms ahead of the main cladding spot, and the post-cooling spot is triggered 1-2ms behind the main cladding spot.

[0018] As a preferred embodiment of the present invention, the thickness of the Möbius topological cladding layer formed in step 3 is 1.5-2.5 mm; the density of the cladding layer after remelting in step 4 is ≥98%, and the bonding strength is ≥90 MPa.

[0019] As a preferred technical solution of the present invention, after laser quenching in step 5, a gradient hardness distribution is formed on the surface of the substrate, wherein the hardness of the substrate is HRC30-35, the hardness of the quenched layer is HRC55-62, and the hardness of the cladding layer is HV700-1050 (equivalent to HRC58-70; when the hardness exceeds the upper limit of the HRC scale, Vickers hardness HV test is used).

[0020] Compared with the prior art, the beneficial effects of the present invention are: 1. Structural Innovation: This invention employs a Möbius topology continuously twisted weld bead structure, which effectively disperses stress and eliminates stress concentration points found in traditional weld beads. Simultaneously, the topological structure forms a biomimetic spiral flow channel, reducing coal and rock adhesion and minimizing adhesive wear. Testing shows that the coal and rock adhesion rate is reduced by more than 60% compared to traditional mesh weld beads.

[0021] 2. Material Innovation: Using Fe55 iron-based material as the matrix, high-cost nickel-based alloys are replaced by micro-alloying elements (Cr, Ni, Mo, Nb, rare earth) compounding. The coating cost is only 30%-50% of that of nickel-based alloy coatings, and the performance is no less than that of nickel-based coatings, with significantly improved corrosion resistance and wear resistance.

[0022] 3. Process innovation: The three-spot gradient heat input realizes the thermal cycle of "preheating-main cladding-slow cooling", avoiding local overheating and rapid cooling caused by single spot, reducing internal stress and crack tendency of cladding layer, allowing powder to melt more fully and the structure to be denser; at the same time, the scanning speed is 20%-30% higher than the single spot process, and the production efficiency is significantly improved.

[0023] 4. Synergistic enhancement: The composite process of three-spot laser cladding and three-spot high-energy beam remelting eliminates defects in the cladding layer, achieves metallurgical densification, and improves the bonding strength by more than 50% compared with traditional cladding; laser quenching forms a gradient hardness layer, which takes into account both high surface hardness and matrix toughness, avoids brittle fracture caused by single quenching, and improves the overall impact resistance and wear resistance of the central groove.

[0024] 5. Superior performance: According to third-party testing, the service life of the central trough reinforced by this method is 3-4 times longer than that of the traditional welded central trough and more than 2 times longer than that of the conventional laser cladding central trough; wear resistance ≤5mg / 1000 times, bonding strength ≥90MPa, salt spray corrosion resistance ≥1200h. All performance indicators are better than the MT / T 153-2011 "Central Trough of Scraper Conveyor" industry standard, and are at the leading level in China and the advanced level in the world. Detailed Implementation

[0025] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be described more clearly and completely below. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0026] This invention provides a technical solution: a method for strengthening the central groove of an iron-based microalloy.

[0027] A method for preparing a steel-based microalloy with a central groove reinforcement includes the following steps: Step 1: Machin the sides of the middle channel and the surface of the chain track to remove oxide scale, oil stains, cracks and burrs. The surface roughness Ra is ≤ 3.2 μm. Then, ultrasonically clean with acetone for 10-15 min and dry for later use.

[0028] Step 2: Using Fe55 iron-based alloy powder as the matrix, prepare microalloyed powder according to the following mass percentages: chromium 12%-18%, nickel 3%-6%, molybdenum 2%-5%, niobium 1.5%-3.0%, rare earth 0.5%-1.0%, with the balance being iron; place the prepared powder in a vacuum drying oven and dry it at 120-150℃ for 2-3 hours to obtain iron-based microalloyed composite powder.

[0029] Step 3: Using a fiber laser and a three-spot shaping module, laser cladding is performed along a Möbius topology scanning path to construct a biomimetic topology cladding layer. The total laser power is 1800-2200W, the preheating spot accounts for 20%, the main cladding spot accounts for 60%, and the post-slow cooling spot accounts for 20%. The scanning speed is 15-25m / min, the main spot diameter is 3-5mm, the preheating / slow cooling spot diameter is 4-6mm, the spot spacing is 2-3mm, the overlap rate is 40%-55%, the Möbius topology twist angle is 15°-30°, and the cladding layer thickness is 1.5-2.5mm.

[0030] Step 4: Perform three-spot high-energy beam remelting on the Möbius topological cladding layer to eliminate pores, cracks and looseness in the cladding layer; the total power is 900-1300W, the preheating spot accounts for 25%, the main remelting spot accounts for 50%, and the densification slow cooling spot accounts for 25%, the scanning speed is 10-20m / min, the working pressure is 50-100Pa, the protective gas is argon, the flow rate is 20-30L / min, and the remelting depth is 0.3-0.5mm.

[0031] Step 5: Perform laser hardening on the non-clad area of ​​the central groove sidewall and the edge of the clad layer to form a gradient hardness layer; wherein, the laser power is 800-1500W, the scanning speed is 5-10m / min, the spot diameter is 6-8mm, and the hardening depth is 0.8-1.2mm.

[0032] Step 6: Mechanically polish the reinforced central groove to remove surface spatter and burrs. Use non-destructive testing to check that the cladding layer and quenched layer are free of cracks and peeling. Once qualified, it is put into storage.

[0033] Example 1: 1. Substrate pretreatment: Select the middle trough of the scraper conveyor with model SGZ764 / 630, and perform turning on the trough side and chain track surface to remove oxide scale and burrs, with a surface roughness Ra=3.0μm; ultrasonic cleaning with acetone for 12min, and drying at 120℃ for 2h.

[0034] 2. Powder preparation: Fe55-based powder was prepared according to the following mass percentages: Cr 15%, Ni 4%, Mo 3%, Nb 2%, rare earth 0.8%, with the balance being Fe. After mixing evenly, the powder was dried at 130℃ for 2.5h.

[0035] 3. Möbius topology three-spot laser cladding: using an IPG YLS-2200 fiber laser + three-spot module, with a total power of 1900W (380W for preheating, 1140W for main cladding, and 380W for post-cooling), a scanning speed of 18m / min, a main spot diameter of 4mm, a preheating / cooling spot diameter of 5mm, a spot spacing of 2.5mm, and an overlap rate of 45%; the Möbius topology twist angle is 20°, with synchronous powder feeding for cladding, and a cladding layer thickness of 2.0mm.

[0036] 4. Three-spot high-energy beam remelting: Electron beam remelting is used, with a total power of 1000W (250W for preheating, 500W for main remelting, and 250W for slow cooling), a scanning speed of 12m / min, a working pressure of 80Pa, an argon flow rate of 25L / min, and a remelting depth of 0.4mm.

[0037] 5. Laser quenching: Laser quenching of the non-cladding area of ​​the groove side, power 1200W, scanning speed 8m / min, spot diameter 7mm, quenching depth 1.0mm.

[0038] 6. Post-processing: Mechanical polishing, UT / PT inspection shows no defects, strengthening is complete.

[0039] In use: The central groove prepared in this embodiment has a dense cladding layer that is metallurgically bonded to the matrix and has a reasonable hardness gradient distribution, making it suitable for coal mining faces with high wear and high impact.

[0040] Example 2: 1. Substrate pretreatment: Select the middle tank of SGZ800 / 1050, process the surface to Ra=2.8μm, ultrasonically clean with acetone for 15min, and dry at 150℃ for 3h.

[0041] 2. Powder preparation: Fe55-based powder formulation: Cr 18%, Ni 6%, Mo 5%, Nb 3%, rare earth 1.0%, balance Fe, dried at 140℃ for 3h.

[0042] 3. Möbius topology three-spot laser cladding: total power 2200W (preheating 440W, main cladding 1320W, post-cooling 440W), scanning speed 22m / min, main spot diameter 5mm, preheating and cooling spot diameter 6mm, spot spacing 3mm, overlap rate 55%; twist angle 30°, cladding layer thickness 2.5mm.

[0043] 4. Three-spot high-energy beam remelting: total power 1200W (preheating 300W, main remelting 600W, slow cooling 300W), scanning speed 15m / min, working pressure 100Pa, argon flow rate 30L / min, remelting depth 0.5mm.

[0044] 5. Laser quenching: power 1500W, scanning speed 10m / min, spot diameter 8mm, quenching depth 1.2mm.

[0045] 6. Post-processing: Polishing + non-destructive testing, qualified products are put into storage.

[0046] In use: The central trough prepared in this embodiment has a higher hardness and better wear resistance in its cladding layer, making it suitable for working conditions with ultra-long working faces and extremely large coal transport volumes.

[0047] Example 3: 1. Substrate pretreatment: Select the middle tank of SGZ900 / 1400, process the surface to Ra=2.5μm, ultrasonically clean with acetone for 15min, and dry at 120℃ for 2h.

[0048] 2. Powder preparation: Fe55-based powder formulation: Cr 12%, Ni 3%, Mo 2%, Nb 1.5%, rare earth 0.5%, balance Fe, dried at 120℃ for 2h.

[0049] 3. Möbius topology three-spot laser cladding: total power 1800W (preheating 360W, main cladding 1080W, post-slow cooling 360W), scanning speed 15m / min, main spot diameter 3mm, preheating / slow cooling spot diameter 4mm, spot spacing 2mm, overlap rate 40%; twist angle 15°, cladding layer thickness 1.5mm.

[0050] 4. Three-spot high-energy beam remelting: total power 900W (preheating 225W, main remelting 450W, slow cooling 225W), scanning speed 10m / min, working pressure 50Pa, argon flow rate 20L / min, remelting depth 0.3mm.

[0051] 5. Laser quenching: power 800W, scanning speed 5m / min, spot diameter 6mm, quenching depth 0.8mm.

[0052] 6. Post-processing: Polishing + non-destructive testing, qualified products are put into storage.

[0053] In use: The central groove prepared in this embodiment, while ensuring high wear resistance, pays more attention to maintaining the toughness of the matrix, and is suitable for working conditions with particularly severe impact loads.

[0054] Performance Testing and Comparative Analysis To verify the technical effect of the present invention, the performance of Examples 1-3 and Comparative Example 1 (traditional manual arc welding, nickel-based alloy powder, parallel straight weld beads) was compared by performance testing. The results are shown in the table below: ; *Note: The reduction rate is calculated relative to the conventional parallel mesh weld (Comparative Example 1).

[0055] Conclusion: The data above shows that the performance indicators of Examples 1-3 of this invention are significantly superior to those of the traditional cladding process (Comparative Example 1). Example 2, by optimizing the powder ratio (increasing the content of Cr, Ni, Mo, and Nb) and process parameters, achieved optimal hardness and wear resistance. Its cladding layer hardness reached HRC80, wear resistance was only 3.8 mg / 1000 cycles, and its service life reached 22 months, more than four times that of traditional cladding. All examples exhibited extremely high bonding strength (≥82 MPa) and excellent corrosion resistance (salt spray test ≥1000 h), and the Möbius topology effectively reduced coal and rock adhesion by more than 60%. This fully demonstrates that this invention, through the synergistic innovation of "structure-materials-process," successfully solved the technical problems of stress concentration, low bonding strength, and short service life in the prior art, achieving a significant improvement in the strengthening effect of the central groove.

[0056] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for strengthening the central groove of an iron-based microalloy, characterized in that: Includes the following steps: Step 1: Machining, cleaning, and drying the surfaces of the middle groove sides and chain track to complete the substrate pretreatment; Step 2: Using iron-based alloy powder as the matrix, add microalloying elements to prepare iron-based microalloyed composite powder; Step 3: Using a three-spot laser cladding process with a Möbius topology scanning path, the iron-based microalloy composite powder is clad onto the surface of the central tank substrate to form a Möbius topology cladding layer. Step 4: Using a three-spot high-energy beam remelting process, the Möbius topology cladding layer is remelted in reverse along the Möbius topology scanning path; Step 5: Laser harden the non-cladding area and the edge of the cladding layer in the middle groove sidewall to form a gradient hardness layer; Step 6: Perform post-processing on the reinforced central groove, including mechanical polishing and inspection.

2. The iron-based microalloy center groove strengthening method according to claim 1, characterized in that: The iron-based microalloy composite powder mentioned in step 2 comprises the following components by mass percentage: 12%-18% chromium, 3%-6% nickel, 2%-5% molybdenum, 1.5%-3.0% niobium, 0.5%-1.0% rare earth elements, with the balance being iron.

3. The iron-based microalloy center groove strengthening method according to claim 2, characterized in that: The rare earth element is a lanthanum-cerium mixed rare earth element.

4. The iron-based microalloy center groove strengthening method according to claim 1, characterized in that: The three-spot laser cladding process described in step 3 has the following parameters: total laser power 1800-2200W, with the preheating spot accounting for 20%, the main cladding spot accounting for 60%, and the post-cooling spot accounting for 20%; scanning speed 15-25m / min; main spot diameter 3-5mm, preheating and cooling spot diameters 4-6mm, spot spacing 2-3mm; overlap rate 40%-55%; and the twist angle of the Möbius topology scanning path 15°-30°.

5. The iron-based microalloy center groove strengthening method according to claim 1, characterized in that: The process parameters for the three-spot high-energy beam remelting described in step 4 are as follows: total power 900-1300W, of which the preheating spot accounts for 25%, the main remelting spot accounts for 50%, and the densification slow cooling spot accounts for 25%; scanning speed 10-20m / min; when using electron beam remelting, the working pressure is 50-100Pa, the protective gas is argon, and the flow rate is 20-30L / min; and the remelting depth is 0.3-0.5mm.

6. The iron-based microalloy center groove strengthening method according to claim 1, characterized in that: The laser quenching process described in step 5 has the following parameters: laser power 800-1500W, scanning speed 5-10m / min, spot diameter 6-8mm, and quenching depth 0.8-1.2mm.

7. The iron-based microalloy center groove strengthening method according to claim 1, characterized in that: In step 3, the three-spot laser cladding uses a fiber laser and a three-spot shaping module. The preheating spot is triggered 1-2ms ahead of the main cladding spot, and the post-cooling spot is triggered 1-2ms behind the main cladding spot.

8. The iron-based microalloy center groove strengthening method according to claim 1, characterized in that: The thickness of the Möbius topological cladding layer formed in step 3 is 1.5-2.5 mm; the density of the cladding layer after remelting in step 4 is ≥98%, and the bonding strength is ≥90 MPa.

9. The iron-based microalloy center groove strengthening method according to claim 1, characterized in that: After laser quenching in step 5, a gradient hardness distribution is formed on the substrate surface, with the substrate hardness being HRC30-35, the quenching layer hardness being HRC55-62, and the cladding layer hardness being HV700-1050 (equivalent to HRC58-70, tested using Vickers hardness HV).